Deductibles in health insurance: Pay or pain? - Geir B. Asheim; Anne Wenche Emblem; Tore Nilssen (University of Oslo, Department of Economics, 2002)
We study a health-insurance market where individuals are o.ered coverage against both medical expenditures and losses in income. Individuals vary in their level of innate ability. If there is private information about the probability of illness and an individual's innate ability is su.ciently low, we find that competitive insurance contracts yield screening partly in the form of co-payment, i.e., a deductible in pay, and partly in the form of reduced medical treatment, i.e., a deductible in pain.
Keywords: D82; I11; 330; health insurance; adverse selection; deductibles; Krankenversicherung; Willingness to pay; Adverse Selection; Asymmetrische Information; Theorie